Rapid assessment of longitudinal systolic left ventricular function using speckle tracking of the mitral annulus - Buß, Sebastian Johannes; Mereles, Derliz; Emami, Mostafa; Korosoglou, Grigorios; Riffel, Johannes; Bertel, Diane; Schönland, Stefan; Hegenbart, Ute; Katus, Hugo; Hardt, Stefan (Clinical research in cardiology, 2012)
Background Evaluation of left ventricular function (LV) is one of the most important tasks of echocardiography. Left ventricular longitudinal function has been recognized to differentiate myocardial disorders better than ejection fraction (EF) alone. But recent parameters are still dependent on image quality and time consuming.